Crystal Plane‐Related Oxygen‐Evolution Activity of Single Hexagonal Co3O4 Spinel Particles. Issue 12 (18th January 2023) - Varhade, Swapnil; Tetteh, Emmanuel Batsa; Saddeler, Sascha; Schumacher, Simon; Aiyappa, Harshitha Barike; Bendt, Georg; Schulz, Stephan; Andronescu, Corina; Schuhmann, Wolfgang
Abstract: The electrocatalytic activity for the oxygen evolution reaction in alkaline electrolyte of hexagonal spinel Co3 O4 nanoparticles derived using scanning electrochemical cell microscopy (SECCM) is correlated with scanning electron microscopy and atomic force microscopy images of the droplet landing sites. A unique way to deconvolute the intrinsic catalytic activity of individual crystal facets of the hexagonal Co3 O4 spinel particle is demonstrated in terms of the turnover frequency (TOF) of surface Co atoms. The top surface exposing 111 crystal planes displayed a thickness‐dependent TOF with a TOF of about 100 s −1 at a potential of 1.8 V vs. RHE and a particle thickness of 100 nm. The edge of the particle exposing (110) planes, however, showed an average TOF of 270±68 s −1 at 1.8 V vs. RHE and no correlation with particle thickness. The higher atomic density of Co atoms on the edge surface (2.5 times of the top) renders the overall catalytic activity of the edge planes significantly higher than that of the top planes. The use of a free‐diffusing Os complex in the alkaline electrolyte revealed the low electrical conductivity through individual particles, which explains the thickness‐dependent TOF of the top planes and could be a reason for the low activity of the top (111) planes. Abstract : SECCM measurements together with SEM and AFM are used to determine the intrinsic activity of two different crystallographic planes available at a single hexagonal Co3 O4 spinel particle.